2020
DOI: 10.1021/acs.macromol.0c02253
|View full text |Cite
|
Sign up to set email alerts
|

Energetics and Mechanisms of poly(N-isopropylacrylamide) Phase Transitions in Water–Methanol Solutions

Abstract: The phase transitions of poly(N-isopropylacrylamide) (PNIPAM) in water−methanol mixed solutions were studied in detail by high-sensitivity differential scanning calorimetry. From this study, the dependences of the transition temperature, enthalpy, heat capacity increment, and width on the methanol molar fraction (x MeOH ) were obtained. The transition temperature passed through a minimum at the methanol molar fraction x MeOH * ∼ 0.35. At x MeOH < x MeOH *, the transition enthalpy decreased quickly with the met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 42 publications
2
19
0
Order By: Relevance
“…They decrease with increasing volume fraction of CD 3 OD, which is in consistency with the computational and experimental calorimetric enthalpies of PNIPAM homo­polymers in water/methanol mixtures. The endothermic enthalpy is related to the heat demanded to break the hydrogen bonds between the polymers and the solvent molecules. ,, As demonstrated in refs and , the presence of CD 3 OD as a cosolvent reduces the number and strength of the hydrogen bonds between the polymers and the solvent molecules during the phase transition, giving rise to lower values of the enthalpy. In methanol-rich solvent mixtures, T onset DSC is 26.1 ± 0.2 °C at 70 vol % of CD 3 OD.…”
Section: Resultssupporting
confidence: 87%
See 2 more Smart Citations
“…They decrease with increasing volume fraction of CD 3 OD, which is in consistency with the computational and experimental calorimetric enthalpies of PNIPAM homo­polymers in water/methanol mixtures. The endothermic enthalpy is related to the heat demanded to break the hydrogen bonds between the polymers and the solvent molecules. ,, As demonstrated in refs and , the presence of CD 3 OD as a cosolvent reduces the number and strength of the hydrogen bonds between the polymers and the solvent molecules during the phase transition, giving rise to lower values of the enthalpy. In methanol-rich solvent mixtures, T onset DSC is 26.1 ± 0.2 °C at 70 vol % of CD 3 OD.…”
Section: Resultssupporting
confidence: 87%
“…Dalgicdir et al found that polymer hydration plays a key role in the co-nonsolvency effect of PNIPAM since methanol geometrically impedes the formation of hydrogen bonding between water and the amide groups of PNIPAM . Grinberg et al performed high-sensitivity differential scanning calorimetry (DSC) measurements and suggested that PNIPAM possesses the cooperative hydrosolvation structures formed by water/methanol complexes, leading to decreasing enthalpies with increasing methanol content . Tavagnacco et al carried out atomistic simulations on a PNIPAM chain in a water/ethanol mixture and found that not only the reduced chemical potential of water in the bulk of the solvent mixture but also the competition between water and ethanol molecules in the interactions with the polymer has a crucial impact on the transition …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Consequently, they are unlikely to be restricted to silk fibroin, but are expected to occur more generally. In this respect, flow-induced fibril formation has recently been observed in various other proteins and peptides [231], with obvious implications for various prion diseases. Indeed, similar effects may also occur with a wider range of water-soluble polymers, such as pNiPAm [232,233].…”
Section: Discussionmentioning
confidence: 96%
“…1a-e Amphiphilic macromolecules used in functional nanomaterials are also called smart polymers, which can respond to heat, 2-5 pH, [6][7][8] light, [9][10][11][12][13] and solvents. [14][15][16] These smart polymers can be applied in the elds of nanosensors, bioimaging, catalysts, etc. Among them, temperatureresponsive copolymers with a lower critical solution temperature (LCST) [2][3][4][5] and upper critical solution temperature (UCST) 17,18 have been studied most widely.…”
Section: Introductionmentioning
confidence: 99%